2015
DOI: 10.1186/s12943-015-0463-5
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental effects limit efficacy of thymoquinone treatment in a mouse model of ovarian cancer

Abstract: BackgroundOvarian cancer is the most lethal gynecologic malignancy, with limited treatment options for chemoresistant disease. An important link between inflammation and peritoneal spread of ovarian cancer is NF-κB signaling. Thymoquinone (TQ) exerts multiple anti-tumorigenic cellular effects, including NF-κB inhibition. We aimed to investigate the therapeutic potential of TQ in an established murine syngeneic model of ovarian cancer.MethodsID8-NGL mouse ovarian cancer cells stably expressing an NF-κB reporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 41 publications
0
35
1
Order By: Relevance
“…This was manifested through stimulation of ascites formation accompanied by elevated NF-κB activity in tumors and macrophages. Importantly, this was contrary to the results of a 10-day TQ treatment, where down-regulation of NF-κB activity was reported along with reduction in tumor mass (Wilson et al, 2015).…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
See 1 more Smart Citation
“…This was manifested through stimulation of ascites formation accompanied by elevated NF-κB activity in tumors and macrophages. Importantly, this was contrary to the results of a 10-day TQ treatment, where down-regulation of NF-κB activity was reported along with reduction in tumor mass (Wilson et al, 2015).…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
“…Collectively, the inhibitory effect that TQ exerts on NF-B activity is another mechanism of action that underlies the anti-cancer potential of TQ and TQ-containing oil and extracts of N. sativa. With that being said, a recent study provides caution regarding the potential use of TQ in clinical trials (Wilson et al, 2015). It highlights the effect of prolonged TQ-treatment (>30 days) as a deleterious factor for its efficacy ACCEPTED MANUSCRIPT…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…An unexpected observation made by our group revealed that inhibition of NF-κB in a syngeneic mouse model of ovarian cancer, increased pro-tumorigenic M2 macrophages, which promoted ascites, an increased expression of pro-tumorigenic soluble factors (such as VEGF in ascites fluid), and an infiltration of more M2 macrophages into the TME [ 48 , 72 ]. These results suggest that the activation of NF-κB in TAMs, not tumor cells, could be a viable therapeutic strategy.…”
Section: Tams As Therapeutic Targetsmentioning
confidence: 99%
“…In this occasion, TQ diminished the expression of iNOS, TNF-α, COX-2, NF-κB and MPO activities [3]. Moreover, TQ is active against breast cancer [83][84][85], ovarian adenocarcinoma [86,87], polycystic ovarian carcinoma [88], cervical squamous carcinoma and prostate [3] cancer. A research findings suggesting TQ at 50 mg/kg/day (p.o.)…”
Section: Tq Effects On the Reproductive System And Fertilitymentioning
confidence: 89%